Phylogeographic Dynamics of Influenza A(H9N2) Virus Crossing Egypt - Li, Ruiyun; Adel, Amany; Bohlin, Jon; Lundkvist, Åke; Olsen, Björn; Pettersson, John H.-O.; Naguib, Mahmoud M. (Frontiers in Microbiology, 2020)
Low pathogenic avian influenza (LPAI) virus of subtype H9N2 is the most frequently detected subtype among domestic poultry and is a public health concern because of its zoonotic potential. Due to the multiple and complex routes of LPAIV H9N2 between geographic regions, little is known about the spatial diffusion of H9N2 virus to, within, and from Egypt, where it is endemic among poultry since 2011. Using close to 800 publicly available hemagglutinin (HA) segment nucleotide sequences, associated location and temporal data, we conducted a Bayesian discrete phylogeographic analysis. Here, we reconstructed and traced the origin, spread and principal transmission routes of H9N2 across large geographical regions, in addition to the transmission between Egypt and the rest of the world and between different Egyptian governorates. Our analysis suggests that during the last few decades, H9N2 has been introduced back and forth continuously between the countries where it is endemic. Amongst these regions, Saudi Arabia, United Arab Emirates and Iraq act as main distribution hubs and drive the viral migration worldwide, with bi-directional and long-distance diffusions. It is noteworthy that H9N2 was introduced once to Egypt via Israel in mid 2009, and that the descendants of the Egyptian LAIVs H9N2 were back-transmitted to Israel in 2015. Additionally, governorates in middle Egypt (Giza, Fayoum and Bani Souwaif) are major hubs in the LPAIV H9N2 transmission network in Egypt. This knowledge highlights that H9N2 is both a global and a national concern and can aid in updating the surveillance programme and vaccine strain selection.